ANALISIS PELAKSANAAN PEMBELAJARAN TAHFIDZ DALAM MENINGKATKAN KONSENTRASI SISWA DI RUMAH TAHFIDZ EL-MUBARAK - Puspita Rilanday, Nindi; Afrizawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of Qur’anic memorization (tahfidz) learning and to identify factors affecting students’ learning concentration at Rumah Tahfidz El-Mubarak, Batam. This research employs a qualitative approach with a field research design. The research subjects consist of students and teachers involved in tahfidz learning activities. Data were collected through observation, documentation, and the researcher’s direct involvement during the Field Experience Program (PLP). Data analysis was conducted through data reduction, data display, and conclusion drawing. The results show that tahfidz learning is carried out through three main stages: tahsin (improving recitation), murajaah (reviewing memorization), and memorization submission using the talaqqi method. Learning is conducted in small groups (halaqah) using an individual approach, which contributes to improving students’ recitation and memorization quality. However, several challenges were identified, including low student concentration, differences in memorization ability, and limited learning time. The study concludes that the success of tahfidz learning is not only determined by the methods used but also by the teacher’s ability to adapt instructional approaches to students’ characteristics. Therefore, more adaptive and varied learning strategies are needed to enhance students’ concentration and learning outcomes.